Focal Narrowing of Retinal Arterioles in Optic Nerve Atrophy - Papastathopoulos, Konstantin I.; Jonas, Jost B. (Ophthalmology (Rochester, Minn.), 1995)
Purpose: To investigate the occurrence of focal narrowing of retinal arterioles in optic neuropathies. Patients and Methods: Color stereo optic disc photographs of patients with primary open-angle glaucoma (n = 114), pseudoexfoliative glaucoma (n = 41), normal-pressure glaucoma (n = 54), ocular hypertension (n = 45), nonarteritic anterior ischemic optic neuropathy (n = 20), descending optic nerve atrophy (n = 60), and control subjects (n = 100) were morphometrically examined in a masked fashion. Focal narrowing of the retinal arterioles was estimated on a scale ranging from 0 to 6. Results: In the control subjects, focal vessel narrowing was significantly and positively correlated with age (P < 0.05). It occurred significantly more often and was more pronounced in eyes with optic neuropathies than in the normal eyes when matched for age. In the eyes with glaucoma, focal narrowing of the arterioles was significantly (P < 0.01) correlated with the degree of optic nerve damage. In addition to a tendency toward a more marked vessel narrowing in the eyes with normal-pressure glaucoma, it did not vary significantly between the various glaucoma types and other optic neuropathies. It was independent of an enlarged parapapillary chorioretinal atrophy. Discussion: Similar to general constriction, focal narrowing of the retinal arterioles is found more frequently and is more marked in eyes with glaucomatous or nonglaucomatous optic nerve damage than in normal eyes. It is correlated with the degree of optic nerve damage, and is typical for optic nerve atrophy, but not pathognomonic for glaucoma.